If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -179 = h + (-219) -179 = h + -219 Reorder the terms: -179 = -219 + h Solving -179 = -219 + h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-1h' to each side of the equation. -179 + -1h = -219 + h + -1h Combine like terms: h + -1h = 0 -179 + -1h = -219 + 0 -179 + -1h = -219 Add '179' to each side of the equation. -179 + 179 + -1h = -219 + 179 Combine like terms: -179 + 179 = 0 0 + -1h = -219 + 179 -1h = -219 + 179 Combine like terms: -219 + 179 = -40 -1h = -40 Divide each side by '-1'. h = 40 Simplifying h = 40
| 3(4x-9)+10=15x+2+7x | | 17g-56=10g-63 | | x^3+7x^2+15x-9=0 | | y*y+9y-10=y*y+4y+3 | | 14y+116=900 | | p+54=4p | | -4y-10=19-2y | | -57+22s=185 | | 5(x-2)+2x=7x+10 | | 6u^2-15u+15=0 | | 29-10z=18z+91 | | 2x+10+6x=34 | | 443=5y+98 | | 30X+20Y=600 | | x+5+11x=12x+y | | -3x+9-5x=-47 | | -437=-112+25t | | (-8)+x=3 | | 172+5z=592 | | 17-6c=47+10c | | 8a+20=15a+55 | | (x+5)+x=27 | | b+9+43=180 | | 3-4c-3= | | 8t+9=97 | | 42.3=1.5d-3.2d | | x/6+2x/3=5 | | 21=2a-4 | | 3(x-4)+x-7=2x+5 | | (x+5)+x= | | (-6x-3)-(5x+10)= | | y=8-2-y |